2009
DOI: 10.1007/s11207-009-9374-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CrH and CrD Molecular Lines in the Sunspot Umbral Spectrum

Abstract: High-resolution Fourier transform spectrometer sunspot umbral spectra obtained at the National Solar Observatory/Kitt Peak were used to identify molecular rotational lines arising from the infrared band systems of CrH and CrD molecules. Measurement of the equivalent width used the Gaussian-profile approximation method, which is suitable especially for faint lines. Equivalent widths are measured for an adequate number of best lines of the A -X (0, 0) band of CrH and the A -X (0, 0; 1, 0) bands of CrD and, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Engvold et al (1980) identified CrH in the spectra of sunspots using the lines of the A-X transition. The presence of CrH molecule in sunspot umbral spectra has been confirmed by Viswanathan et al (2009). Also CrH molecular bands have been identified in the spectra of very low mass stars, brown dwarfs and substellar objects (Basri 2000).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Engvold et al (1980) identified CrH in the spectra of sunspots using the lines of the A-X transition. The presence of CrH molecule in sunspot umbral spectra has been confirmed by Viswanathan et al (2009). Also CrH molecular bands have been identified in the spectra of very low mass stars, brown dwarfs and substellar objects (Basri 2000).…”
mentioning
confidence: 67%
“…The majority of these band lines are also severely blended with TiO molecular lines. These temperatures lead to an average value of effective rotational temperature of 2169 K. The effective temperature has been estimated for A 6 + -X 6 + (0, 0) bands with integer rotational quantum numbers of CrH molecule to be 1412 ± 29 K by Viswanathan et al (2009). The average temperature of the FeH molecule for the two P (J ) branches of the (7/2-7/2) sub band in the (0, 0) transition is 1740 ± 100 K reported by Mulchaey (1989) and the majority of the molecular lines are also severely blended with other molecular and atomic lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromium hydride has been observed for many years in the photospheres of S-type stars and sunspots via the electronic transition A 6 Σ + −X 6 Σ + , measured in absorption (Lindgren & Olofsson 1980;Viswanathan et al 2009). The molecule in fact has been found to be an excellent indicator of L-type brown dwarfs (Kirkpatrick et al 1999a(Kirkpatrick et al , 1999bBurrows et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Viswanathan et al [11] have identified the CrH and CrD molecular lines in sunspot umbral spectrum. Pavlenko et al [12] have reported equilibrium studies of MgH, MgD, CrH and CrD molecules.…”
Section: Introductionmentioning
confidence: 99%